مدخل مقترح لتكييف تطبيق المعايير الدولية للتقارير المالية IFRs في الدول النامية اقتصادياً: دراسة الحالة السورية نموذجاً - البهلول, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This paper is concerned with the regulation of international accounting and the difficulties that condition its successful implementation, particularly in the context of developing countries such as The Syrian Arab Republic. Although international bodies are devoted to internationalize accounting practices, most studies have acknowledged the international differences in accounting, which are attributed to the fact that national accounting systems are consequences of environmental factors (economic, political, professional and cultural) in which they are developed. As a result, it is possible to hypothesize that the problem of appropriate accounting standards will imply a different norm of compliance and practices of IASs/IFRs. Consequently, this research suggests an adaptation or customization approach to meet the local needs of cultural, political, economic and other environmental factors in Syria. يهدف هذا البحث إلى اقتراح عدم تطبيق المعايير الدولية للتقارير المالية دون تكييفها بما يتلائم مع البيئة القانونية و المهنية و الاقنصادية في سوريا. حيث يناقش التناغم الدولي لمعايير المحاسبة و الصعوبات التي تعيق تطبيقها الناجح لاسيما في الدول النامية. و على الرغم من جهود المنظمات الدولية المكرسة لتوحيد الممارسة المحاسبية على المستوى الدولي, اعترفت معظم الدراسات باختلاف الممارسات المحاسبية دولياً. و لقد عزي السبب إلى أن الأنظمة المحاسبية الوطنية هي ناتج العوامل البيئية التي تطورت ضمنها (اقتصادية, سياسية, مهنية, ثقافية, و قانونية الخ...). و بالنتيجة, يبين هذا البحث أن مشكلة معايير المحاسبة الملائمة سوف يعني ضمناً أساليب مختلفة من الالتزام و الممارسات عند تطبيق المعايير الدولية للتقارير المالية (معايير المحاسبة الدولية). وبناء عليه, يقترح أن المدخل المناسب لتطبيق المعايير الدولية هو تعديلها أو تكييفها بما يتلائم مع محددات بيئة الأعمال السورية (الاقتصادية, السياسية, الثقافية, الخ...)